Antibody neutralization of a myotoxin from the venom of Bothrops asper (terciopelo) - Lomonte, Bruno (1987)
Neutralization of biological activities of B. asper myotoxin by a monospecific anti-myotoxin rabbit serum and polyvalent antivenom was studied. Both antisera neutralized myotoxic, phospholipase A and lethal activities of myotoxin, whereas edema-forming activity of myotoxin was not neutralized by these antisera. Anti-myotoxin rabbit serum neutralized most of the myotoxic activity of B. asper venom, but did not neutralize phospholipase A activity of this venom. Neutralization curves showed that myotoxicity induced by myotoxin persisted at antivenom/toxin or antiserum/toxin ratios at which phospholipase A activity was completely neutralized. This suggests that myotoxicity does not depend upon enzymatic activity of the toxin. Antiserum to myotoxin neutralized approximately 70% of myonecrosis induced by crude B. asper venom. This demonstrates that myotoxin is the main factor responsible for the development of myonecrosis in envenomations by B. asper.